A review of countermeasures for snowboarding injuries - Kelsall, H.; Finch, C. (1996)
Snowboarding is quickly becoming a popular sport at alpine resorts. In contrast to alpine siding, where injuries to the knee and thumb are most common, the wrist (and forearm) and ankle are the most frequently injured body regions for snowboarders. General guidelines for snowboarding safety are available and are similar to the recommendations for general snow/ski safety. Unfortunately, the rapid international growth of the sport has not been matched by detailed epidemiological evaluation of the injuries specific to snowboarding or the countermeasures to prevent them. The aim of this report is to critically review the literature describing injury prevention measures, or countermeasures, for snowboarding. In doing so, it provides an evaluation of the extent to which these countermeasures have been demonstrated to be effective. Few countermeasures specific for snowboarding were found to have been formally demonstrated to actually prevent injury. The countermeasures to which some attention has been paid are boots, bindings, wrist guards, skill level and methods of failing. Skill level and the other injury countermeasures apply more generally across the sport. Recommendations for countermeasure implementation include: education for snowboarders, adherence to snow conduct and safety codes, preparing snowboarders for their activity and maintenance of parks and runs. Recommendations for improved data collections include: maintaining existing data collections, collecting information about equipment used by snowboarders. Further biomechanical and epidemiological research needs to be undertaken on knee/ankle and wrist/forearm injuries. Evaluation of countermeasures needs to keep pace with the rapid developments in this field. Particular attention should be directed towards evaluations of the role of wristguards, boots/bindings, fall technique and lessons in preventing injuries. Given the rapidly increasing popularity of the sport, the need for the safety equipment to be evaluated would seem to be a priority, along with identifying the echanisms of injury.